Structure of early lexicon: Should first vocabulary be categorized as adults? - Kovačević, Melita (Array, 2000)
The course of early lexicon development is significantly constrained by the number of factors, such as child's cognitive development, its capacity for analysing and modifying internal representations and linguistic input itself. Acquisition of first words and their meanings is complex process and there are clear reasons to approach its structure differently than in adult word system. Over the last twenty years various different theoretical concepts were given in order to explain various phenomena typical for early lexical development. In this paper we will present a lexical analysis of children spontaneous speech samples of two children, transcribed within the CHILDES system (MacWhinney 1990). Language data are longitudinal and have been collected on week to week basis, which enables us to follow very early lexical development, starting from prelexical phase to first words. Our focus will be given on manner of classification of the children's first vocabulary and how the proposed classification departs from a formal adults grammar. A possible justification of the approach will be provided along with a discussion of language universals vs. language specifities.